Role of imaging (MDCT) in ocular and orbital lesions - Shah, Pratima Kumari; Rauniyar, RK; Gupta, MK; Badhu, BP (Health Renaissance, 2017)
Background: Radiological imaging is still important to diagnose ocular and orbital abnormalities. Computed tomography is the first-line imaging modality for orbital imaging in the acute setting with magnetic resonance imaging playing an important secondary role. Objective: To assess the role of multidectector computed tomography (MDCT) in diagnosis of ocular and orbital lesions. To describe the imaging features of various orbital and ocular lesions on MDCT. Methods: A prospective cross-sectional study was conducted on 50 patients in B.P. Koirala Institute of Health Sciences, over the period of one year (from July 2013 to June 2014). All the patients with clinical suspicion of ocular and orbital lesions, referred from the ophthalmology department for CT scan were included in this study. Results: Out of 50 cases 4 were traumatic and 46 were non traumatic cases. Retinoblastoma was most common non traumatic lesion in our study. We compared MDCT diagnosis and final diagnosis which was based on histopathology/ per operative finding, FNAC, clinical response to treatment, supportive laboratory (biochemical/ microbiological) findings and supportive findings on other radiological investigations (USG and MRI). The sensitivity of MDCT in diagnosing ocular and orbit lesions was 95.65%. Conclusion: MDCT has important role in characterization and diagnosis of the lesions, surgical planning and follow up of patient with various ocular and orbital pathologies. MDCT is better for evaluation of bones and detection of calcifications and to discern the location, extent and configuration of the lesions. Therefore MDCT is an ideal radiological method for evaluation of various ocular and orbital lesions. Health Renaissance 2015;13 (3): 24-36